Կաթողիկոսական ընտրութեան կարգը՝ըստ մատենագրական տեղեկութիւնների եւ Մաշտոց ծիսամատեանների - Սարգսեան, Եղիշէ սրկ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В Армянской Церкви издавна существовали определённые формы и правила избрания Католикоса. Историки зафиксировали этот процесс в своих трудах, поскольку в Средние века Католикосы Армении избирались, как правило, церковными и национально-церковными собраниями. Эти собрания созывались либо по инициативе влиятельного князя, либо по приглашению короля. В некоторых случаях князья или короли вмешивались в процесс избрания Католикоса, а иногда подобное вмешательство исходило и от иностранных правителей, что было обусловлено историческими и политическими реалиями данного периода. The Armenian Church had established procedures and regulations for the election of the Catholicos. Historians have documented the process of Catholicosal elections, noting that in the Middle Ages, the Catholicos of Armenia was primarily chosen by ecclesiastical and national-church assemblies. These assemblies could be convened either by an influential prince or at the invitation of the king. There were instances in which local princes or kings interfered in the election of the Armenian Catholicos, as well as cases where foreign rulers influenced the process. Such interference was shaped by the historical and political context of the time.
Keywords: Կրօնագիտութիւն